Hak-hak Perempuan dalam Perspektif al-Qur’an - Roikhatul Jannah (At-Ta'wil: Jurnal Pengkajian al-Qur'an dan at-Turats, 2019)
Islamic teachings essentially do not distinguish between the rights of women and men in married life and in social life. In the Qur'an many meet in verses about respect for women's rights. By doing a textual interpretation it can be seen that women also have rights as men, although on certain matters there are not the same, this is due to the main functions and duties that in men. In Islam women also have rights as men, but in certain cases there are not the same, this is due to the main functions and tasks held by men. Among the rights of women are: the right to get an education, the right to get a dowry and a living, the right to ask for divorce when sufficient conditions and if passed will cause harm, rights in the field of inheritance and material rights.